Zoonosis and zooanthroponosis of emerging respiratory viruses - Khalil, Ahmed Magdy; Martinez-Sobrido, Luis; Mostafa, Ahmed (Frontiers in Cellular and Infection Microbiology, 2024)
Lung infections in Influenza-Like Illness (ILI) are triggered by a variety of respiratory viruses. All human pandemics have been caused by the members of two major virus families, namely Orthomyxoviridae (influenza A viruses (IAVs); subtypes H1N1, H2N2, and H3N2) and Coronaviridae (severe acute respiratory syndrome coronavirus 2, SARS−CoV−2). These viruses acquired some adaptive changes in a known intermediate host including domestic birds (IAVs) or unknown intermediate host (SARS-CoV-2) following transmission from their natural reservoirs (e.g. migratory birds or bats, respectively). Verily, these acquired adaptive substitutions facilitated crossing species barriers by these viruses to infect humans in a phenomenon that is known as zoonosis. Besides, these adaptive substitutions aided the variant strain to transmit horizontally to other contact non-human animal species including pets and wild animals (zooanthroponosis). Herein we discuss the main zoonotic and reverse-zoonosis events that occurred during the last two pandemics of influenza A/H1N1 and SARS-CoV-2. We also highlight the impact of interspecies transmission of these pandemic viruses on virus evolution and possible prophylactic and therapeutic interventions. Based on information available and presented in this review article, it is important to close monitoring viral zoonosis and viral reverse zoonosis of pandemic strains within a One-Health and One-World approach to mitigate their unforeseen risks, such as virus evolution and resistance to limited prophylactic and therapeutic interventions.